Filling in the Gaps: Memory Implications for Inferring Missing Content in Graphic Narratives. Issue 8 (17th November 2017) - Magliano, Joseph P.; Kopp, Kristopher; Higgs, Karyn; Rapp, David N.
Abstract : Visual narratives, including graphic novels, illustrated instructions, and picture books, convey event sequences constituting a plot but cannot depict all events that make up the plot. Viewers must generate inferences that fill the gaps between explicitly shown images. This study explored the inferential products and memory implications of processing gaps in visual narratives. Participants viewed picture-stories containing event sequences comprised of beginning, bridging, and end states and the presence of these event state panels was systematically manipulated. The pattern of processing times after omitted event panels suggests that participants inferred missing beginning and bridging states but not missing end states. In a recognition test including both seen and unseen event panels, participants' memories were most accurate for end state events. The results suggest that generating inferences distorts memory for explicit content, particularly content that has a high semantic overlap with potentially constructed inferences.